THEMATIC HADITH STUDY ON NISHAB DETERMINATION FOR CURRENCY ZAKAT: Textual Analysis and Contemporary Application - Arfan, Nuril Aisyah; Mubarok, Mohammad Nabil Iklil; Wahyuni, Sri; Solihin, Mohammad Muchlis (El-Waroqoh : Jurnal Ushuluddin dan Filsafat, 2025)
Contemporary challenges in determining zakat nishab for fiat currencies necessitate rigorous return to foundational scriptural sources through systematic thematic hadith analysis. This research employs classical hadith criticism methodology takhrij al-hadith, naqd al-sanad, naqd al-matan, and syarah hadith to examine authenticated prophetic traditions regarding gold and silver thresholds from primary compilations (Kutub al-Sittah). Comprehensive sanad evaluation reveals all narrators meet tsiqah criteria with unbroken transmission chains, while matan analysis confirms consistency with Qur’anic principles and absence of shadhdh or ‘illah. Thematic synthesis across four authenticated traditions demonstrates silver's (200 dirhams) explicit textual primacy as nishab standard, though gold (20 dinars) maintains legitimate alternative status. Jurisprudential implications extend beyond quantitative parameters to underlying hikmah: nishab functions as capacity filter protecting vulnerable populations while actualizing redistributive justice. The integrative qiyas framework (al-badl lahu hukm al-mubdal) legitimizes contemporary currency zakat by functional equivalence rather than material identity. This study’s primary contribution lies in demonstrating how rigorous hadith methodology generates contextually-responsive yet scripturally-grounded solutions for modern fiqh challenges. Empirical observation at UIN Madura validates theoretical findings’ practical relevance while revealing implementation gaps requiring comprehensive governance reforms. However, the core scholarly value resides in establishing methodologically-sound hadith analysis as essential foundation for contemporary zakat jurisprudence.